Single stack performance using chromium carbide (Cr‒C) and niobium carbide (Nb‒C) coated on 316 L bipolar plates - Nur Fawwaz Asri,; Teuku Husaini,; Abu Bakar Sulong,; Edy Herianto Majlan,; Wan Ramli Wan Daud, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Metallic bipolar plates tendency to have high contact resistance and corrosion after several times of usage affected performance of a cell in PEMFC stack. Thisstudy focused on the interfacial contactresistance (ICR) and corrosion resistance of SUS 316 L bipolar plates using Cr‒C and Nb‒C as coating layer, single stack performance in PEMFC were observed by experimental. The Cr‒C and Nb‒C coating layer acted as protective layer between SUS 316 L bipolar plates. Therefore, coating is a method in preventing the bipolar plates surface material from damage in the acidic environment of PEMFC. To develop corrosion-resistant and high conductivity bipolar plates for PEMFC, the coatings bipolar plates were applied to cell fabrication in comparison with bare SUS 316 L bipolar plates. The SUS 316 L bipolar plates size and electrode area were 50 mm2 and 25 mm2 , respectively. The experiment was carried out on a prepared assembled single cell bipolar plates with the commercial membranes, conductive carbon papers and gasket. Initial performance of the single cells using Cr‒C and Nb‒C coatings over SUS 316 L bipolar plates were recorded at a cell voltage between 0.4 V to 0.5 V, respectively. In comparison, Nb‒C gives good performance of corrosion resistance and the ICR value as low as 10‒12 A/cm2 and 1.22 mΩ cm−2. Additionally, it gives maximum power density of 137 mW/cm2 at the cell voltage 0.51 V. The lifetime durability of the single cell significantly improved from the uncoated current density of 390 mA/cm2 to 450 mA/cm2 with Nb‒C coating layer.